Oriented co-continuous 3D porous scaffolds with inhibited activating functionality: An effective strategy to inhibit the hyperactivation of astrocytes. (January 2022) - Zhao, Baisong; Wei, Xin; Wang, Qingning; Liu, Ya-Hui; Zheng, Zi-Li; Liu, Zhou-Yun-Tong; Li, Ka; Dai, Rui; Xu, Jia-Zhuang; Li, Zhong-Ming; Song, Xingrong
Graphical abstract: Highlights: Oriented pore architecture provides a physical cue to inhibit the proliferation and overactivation of astrocyte. The expression of growth factors and inflammatory factors was down-regulated via the suppression of the Wnt/β-catenin signal pathway. Inhibiting of astrocyte activation caused by oriented pores was attributed to the blocking of cell interaction. The anisotropic scaffold shows a promising non-pharmacologic alternative to suppress neuropathic pain. Abstract: Astrocyte activation is an important cause of neuropathic pain. Inhibiting the hyperactivation of astrocytes is beneficial to control over neuropathic pain. However, there is a lack of non-pharmaceutical ways to inhibit the hyperactivation of astrocytes. This study aimed at regulating the activity of glial cells via the architecture of 3D porous scaffolds. Herein, the 3D porous scaffolds with co-continuous and oriented pores were prepared via solid-phase stretching of co-continuous polymer blends followed by selective phase extraction. Compared to the isotropic scaffold, the proliferation of astrocytes slowed down on the oriented scaffolds. Meanwhile, the expression of growth factors and inflammatory factors secreted by astrocyte activation was inhibited by the oriented pores. It led to the suppression of the Wnt/β-catenin signaling pathway that is crucial to determine chronic neuropathic pain. Immunofluorescence staining displayed that the hyperactivation of astrocytes was inhibited, and the expression of kindlin-1, a key protein that activates astrocytes, was downregulated. The proposed strategy offers a probable physical means to relieve neuropathic pain.